Adherence to osteoporosis pharmacotherapy one year after osteoporotic fracture – a Swiss trauma centre secondary prevention project (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY According to current evidence, one out of ten fracture patients with osteoporosis does not sustain another fracture if he or she is on adequate medication. However, epidemiological surveys show that only about 15 to 30% of affected patients avail themselves of the treatments. This cohort study investigated how many fracture patients with a recommendation for antiosteoporotic therapy effectively received treatment and the possible reasons why the treatment was not implemented. METHODS As part of a quality improvement programme in a Swiss trauma centre, fracture patients were actively checked for osteoporosis in accordance with a standardised outpatient programme. The results, together with detailed therapy recommendations, were transmitted to each patient’s general practitioner (GP). A prospective questionnaire survey evaluated all patients with a diagnosis of osteoporosis for subsequent realisation of therapy 1 year after the fracture (mean ± standard deviation; chi-square; analysis of variance; significance level p